IMPLEMENTASI MEDIA SCRABBLE DALAM PENGUASAAN KOSAKATA BAHASA ARAB SISWA KELAS VII MTS NEGERI 5 JEMBER - Ainun Nafisah Nafisah; Muhammad Nidom Hamami Abicandara; Irwan S Sofiyanto (Program Studi Pendidikan Agama Islam, 2024)
Learning Arabic is one of the foreign language subjects at school and only a few students are able to master Arabic, even in written and reading form. The weakness of students in general is the lack of vocabulary. Meanwhile, mastery of vocabulary in learning Arabic is very important to support language proficiency. Therefore, to make it easier for students to learn and understand vocabulary, a medium is needed to train and teach the vocabulary, one of which is by using Scrabble. Scrabble is a medium used to develop language skills, one of which is vocabulary mastery. The Scrabble game has several benefits, one of which is increasing vocabulary because in this game students are required to arrange letters to form vocabulary so that students are able to remember vocabulary well. This research is descriptive qualitative research. The research objects were students in class VII A of MTs Negeri 5 Jember. The results of this research show that the media used by teachers in learning Arabic are textbooks and LCD. The implementation of Scrabble media is carried out by dividing students into several groups, each group gets a letter. Then the researcher instructed the students to stick the letters on the Scrabble board that had been prepared by the researcher. The results of the application of Scrabble learning media show that class VII A MTs Negeri 5 Jember masters more vocabulary and can increase their vocabulary and are able to remember vocabulary words well.